Particulate Matter 2.5 Exposure and Self-Reported Use of Wood Stoves and Other Indoor Combustion Sources in Urban Nonsmoking Homes in Norway. - Annah B Wyss; Anna Ciesielski Jones; Anette K Bølling; Grace E Kissling; Ryan Chartier; Hans Jørgen Dahlman; Charles E Rodes; Janet Archer; Jonathan Thornburg; Per E Schwarze; Stephanie J London (PLoS ONE)
Few studies have examined particulate matter (PM) exposure from self-reported use of wood stoves and other indoor combustion sources in urban settings in developed countries. We measured concentrations of indoor PM < 2.5 microns (PM2.5) for one week with the MicroPEM™ nephelometer in 36 households in the greater Oslo, Norway metropolitan area. We examined indoor PM2.5 levels in relation to use of wood stoves and other combustion sources during a 7 day monitoring period using mixed effects linear models with adjustment for ambient PM2.5 levels. Mean hourly indoor PM2.5 concentrations were higher (p = 0.04) for the 14 homes with wood stove use (15.6 μg/m3) than for the 22 homes without (12.6 μg/m3). Moreover, mean hourly PM2.5 was higher (p = 0.001) for use of wood stoves made before 1997 (6 homes, 20.2 μg/m3), when wood stove emission limits were instituted in Norway, compared to newer wood stoves (8 homes, 11.9 μg/m3) which had mean hourly values similar to control homes. Increased PM2.5 levels during diary-reported burning of candles was detected independently of concomitant wood stove use. These results suggest that self-reported use of wood stoves, particularly older stoves, and other combustion sources, such as candles, are associated with indoor PM2.5 measurements in an urban population from a high income country.